1999
DOI: 10.1590/s1516-35981999000600034
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da suplementação com feno de Leucena (Leucaena leucocephala (Lam) de Wit) durante a estação seca sobre o desenvolvimento ponderal de ovinos

Abstract: RESUMO -O objetivo deste experimento foi estudar o desempenho de borregos suplementados com dois níveis de feno de leucena (Leucaena leucocephala (Lam) de Wit), durante a estação seca, em comparação com animais mantidos em pastagem exclusiva de capimbuffel (Cenchrus ciliaris, L) ou em pastagem consorciada de capim-buffel com guandu (Cajanus cajan). Durante a estação das águas, foi determinado ainda o desempenho dos animais que foram mantidos em pastagem comum de capim-buffel, sem suplementação. Os seguintes tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
9

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 2 publications
1
2
0
9
Order By: Relevance
“…1) is in accordance to the results obtained by Moreira et al (2007) who evaluated productive potential of dormant buffel grass and reported forage mass values of 3,076 to 3,118 kg of DM ha -1 during November and December in Brazilian Northeast semi-arid. Proportion of leaves, stems and dead material were similar to the results found by Souza and Espíndola (1999). In the initial phase of this trial, the leaf fraction corresponded to 28% of forage mass while the stem and dead material corresponded to 60% and 12% of forage mass, respectively.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…1) is in accordance to the results obtained by Moreira et al (2007) who evaluated productive potential of dormant buffel grass and reported forage mass values of 3,076 to 3,118 kg of DM ha -1 during November and December in Brazilian Northeast semi-arid. Proportion of leaves, stems and dead material were similar to the results found by Souza and Espíndola (1999). In the initial phase of this trial, the leaf fraction corresponded to 28% of forage mass while the stem and dead material corresponded to 60% and 12% of forage mass, respectively.…”
Section: Resultssupporting
confidence: 86%
“…Buffel grass (Cenchrus ciliaris L.) is one of them (GUIMARÃES FILHO;SOARES, 1999;SOUZA;ESPÍNDOLA, 2000;SANTOS et al, 2005). According to Souza and Espíndola (1999) this pasture may produces more than 4,500 kg year -1 of dry matter. On the other hand, in the dry rainy or in dry period of year this forage may show poor quality affecting productive performance of animals (SOUZA; ESPÍNDOLA, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…A porcentagem de PB foi inferior ao valor de 23,6% obtido por Souza & Espíndola (1999), no feno de leucena, sendo superior, no entanto, aos obtidos por Camurça et al (2002), nos fenos de capim-elefante (6,68%) e capim-bufel (9,03%), destacando-se também em relação aos encontrados por Wanderley et al (2002) e Andrade et al (2002), na palma forrageira (4 a 6%). Foi superior ainda aos valores descritos por Neumann et al (2002), de 7,62% em silagem de sorgo, e por Reis et al (2001), de 10,2 e 6,9% para silagens de milho úmido e de milho hidratado, respectivamente.…”
Section: Resultsunclassified
“…Nesse cenário, pesquisadores têm trabalhado com duas situações aparentemente distintas, de modo que determinada tecnologia parece não ser adequada para todo o Nordeste: na primeira situação, estudiosos defendem estratégias para crescimento e ganho de peso na época seca do ano, como Souza & Espíndola (1999), cujos resultados parecem mais recomendados para localidades de climas mais favoráveis e para propriedades mais tecnicamente equipadas; na segunda, incluem-se aqueles que consideram que, na época seca, é mais importante a mantença dos animais.…”
Section: Introductionunclassified
See 1 more Smart Citation